High-viscosity injector-based pink-beam serial crystallography of microcrystals at a synchrotron radiation source. (2019) - Martin-Garcia, Jose M.; Zhu, Lan; Mendez, Derek; Lee, Ming-Yue; Chun, Eugene; Li, Chufeng
No abstract available